Geochemistry of the black rock series of lower Cambrian Qiongzhusi Formation, SW Yangtze Block, China: Reconstruction of sedimentary and tectonic environments - Liu Hao (De Gruyter, 2021)
The black rock series in the Qiongzhusi Formation contains important geochemical information about the early Cambrian tectonic and ecological environment of the southwestern Yangtze Block. In this paper, major, trace, and rare earth element data are presented in an attempt to reveal the sediment source during the deposition of the early Cambrian Qiongzhusi Formation and to reconstruct the sedimentary tectonic environment and weathering intensity during that time. The basin primarily received continental clastic material with neutral-acidic igneous rocks from a stable source and with a moderate level of maturity during the depositional period of the Qiongzhusi Formation. Furthermore, the strata were weakly influenced by submarine hydrothermal fluids during diagenesis. The reconstruction of the sedimentary environment and weathering intensity shows that P2O5 enrichment and water body stratification occurred due to the effects of upwelling ocean currents during the depositional period of the Qiongzhusi Formation. The combination of upwelling and bottom-water hydrothermal fluids led to environmental changes in the study area, from dry and hot to moist and warm. Last, the reconstruction of the tectonic environment of the Qiongzhusi Formation indicates that deposition occurred in continental slope and marginal marine environments associated with a continental arc tectonic system. These findings provide an essential basis for the comprehensive reconstruction of the early Cambrian sedimentary environment of the Yangtze Block.